Multisystem Inflammatory Syndrome in Children: A Review - Chandni P. Daryanani; Theresia Monica Rahardjo; Harris Utama; Angga Trie Buana; Eaufira Mereditha Pasaribu; Euodia Eunike (Rumah Sakit Unggul Karsa Medika, 2023)
Pediatric inflammatory multisystem syndrome, temporally associated with SARS-CoV-2 (PIMS-TS) or multisystem inflammatory syndrome in children (MIS-C) is a condition identified recently. Children who were previously healthy may experience cardiac, neurological, respiratory, gastrointestinal, and dermatological dysfunction. Majority of patients (73%) require intensive care treatment, and more than half (56%) of patients arrive in shock. Different management are used for MIS-C patients, but they all primarily focus on immunomodulatory drugs such as IVIG and glucocorticoids as initial therapy. Biologic agents like anakinra, tocilizumab, and infliximab should be intensified when the patients are resistant to IVIG and glucocorticoids.